Skin-inspired flexible tactile sensing devices - Zhu, Bowen (2016)
The human body is covered in skin which contains a variety of sensory receptors accounting for one’s ability to sense objects physical properties. Receptors in skin respond to external stimuli and thus allow humans to perceive the sensations so as to recognize the surrounding environment and conduct daily activities. The exquisite sensations of the natural skin have inspired the rise of highly sensitive tactile sensing devices that could emulate the tactile sensation of natural skin. Herein, this thesis is engaged in developing materials and engineering ways to design and integrate high performance tactile sensing devices to mimic and emulate the sense of touch in human. To devise high performance tactile sensors capable of emulating the exquisite tactile sensation of natural skin, anisotropic microstructures are introduced to pressure-response layers, which could serve as a universal approach to improve the sensitivity of tactile sensors. Two kinds of microstructured pressure-sensitive layers, namely graphene/PDMS and AgNWs/PDMS, are developed and applied in resistive tactile sensors. Both of the pressure-sensitive layers can be obtained by facile methods with high uniformity of patterns and large-scale fabrication capability. By virtue of anisotropic effect, the microstructured tactile sensors demonstrate high sensitivity in low pressure range, fast response time, and great stability, which are important parameters for mimicking tactile sensing in natural skin. The sensitivity of sensors can be tuned by modifying the parameters of microstructure patterns, shedding light on the application of the sensors in diverse sensing environments that require different tactile sensitivities. Also, the microstructured sensor illustrates remarkable capability of encoding tactile sensations and measuring pulse wave, demonstrating great potential for applications in information transmission and health monitoring. With the achievement of highly sensitive tactile sensors, a further attempt is to mimic the sensory memory of human. Electrically configurable memory devices are integrated with resistive tactile sensors to address the retention of sensations after stimuli cease. External pressure can be detected and transduced to the different resistance states of the memory devices. Applied pressure distribution can be detected and retained in the memory device arrays for a long time by virtue of the nonvolatile memory performance. The integrated device can be programmed by the touch of a finger, showing great potential in sensing and retaining the tactile sensations for mimicking the human sensory memory. To develop interactive tactile sensing devices for next-generation sensory memory devices, electrochromic devices are integrated with resistive tactile sensors to produce human-readable outputs. The low operation voltage for color switching of the electrochromic material renders it possible to transduce applied pressure into visible color change. Electrodeposited tungsten trioxide films are selected as the electrochromic material to integrate with pressure sensors because of their great color memory effect. The integrated device can retain the tactile sensation information without power supply after stimuli ceased.